Knowledge of Oral Prophylaxis and Dental Check-up Amongst Primary School Teachers in Lagos State: An Urban-rural Comparative Study - Babalola Castano; Adepeju Sanni; Titilayo Dawodu; Olusoji Olanrewaju; Akinwale Oguntimehin (Nigerian Dental Journal)
ABSTRACT